Ugandan Health Care Professionals’ Response to Sexual Violence Survivors: Exploring Local Strategy and International Guidelines - Fay, Kathryn E. (Journal of interpersonal violence, 2021)
This survey-based study gathered information on health professionals’ attitudes and behaviors regarding victims of sexual assault, focusing on the applicability and utility of best practices put forth by the World Health Organization and the United Nations. This cross-sectional study involved a self-administered, 84-question survey to health care professionals affiliated with Mulago National Referral and Kayunga Hospitals in Uganda. The survey included demographic questions as well as questions about participants’ attitudes toward sexual violence and the role of HPs in addressing sexual violence. The remainder of the survey transformed two sets of international guidelines into a series of statements with which participants could agree or disagree using a Likert-type scale. In total, 75 partially or fully completed surveys were collected, 45 from Mulago, and 30 from Kayunga. A minority of participants indicated that the guidelines were unrealistic (4.1%) or culturally inappropriate (14.1%). Most HPs agreed (91.8%) with the key components of recommended care. However, many respondents highlighted the need for additional training (68%). Nearly half of participants were uncertain or disagreed that there was a clear protocol for care of survivors of sexual violence (48%). Targets for improvement identified by participants included enhanced support of staff, access to resources, and relationships with community partners. Ugandan HPs have been receptive to the World Health Organization and United Nations guidelines. The majority of participants felt that the guidelines were realistic and culturally appropriate. Furthermore, many of these guidelines have been implemented. However, additional steps identified by Ugandan health workers could be undertaken to further improve the care received by survivors of sexual violence.